Warm Ginger Compress and Static Stretching for The Change of Pain in Gout Arthritis - Caturia Sasti Sulistyana; Satria Eureka Nurseskasatmata; Abdul Fauzi (STIKes Patria Husada Blitar, 2023)
Gout Arthritis is a joint inflammation resulted from excessive levels of the uric acid in the blood. The characteristic of the symptoms was monoarticular, swollen, reddish, and pain that interferes activity These conditions need therapy because it could affect the quality of life. The non-pharmacological therapy that can be given was the combination of warm ginger compress and static stretching. The purpose of this research was analyzing the effectiveness of the combination of warm ginger compress and static stretching for change pain in gout arthritis. This research used Randomized Controlled Trial (RCT) method to 30 people with gout arthritis in Tambaksari Surabaya. This research used simple random sampling technique. The respondents were divided into two groups, control and treatment group were also determined randomly. The intervention was given for 15-20 minutes, 6 times in 2 weeks. The data analysis used t-test 2 sample. The result of t-test in the intervention group revealed that there was change pain before and after given intervention while the independent sample showed that there was difference in pain in both groups. The warm ginger compress therapy caused vasodilation blood vessel so as to prevent spasm of the muscles, while static stretching through relaxation muscles so increased physical relaxation. The both intervention were useful as non pharmacology therapy to reduce pain in people with gout arthritis.